The Pauline writings an annotated bibliography - Seifrid, Mark A.; Tan, Randall K.J., 1974- (Grand Rapids, MI Baker Academic, 2002)
Includes index.
Keywords: Bible. N.T. Epistles of Paul -- bibliography